2016
DOI: 10.1111/jfs.12306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natamycin edible films fortified with essential oils on the safety and quality parameters of Kashar cheese

Abstract: Effects of the edible films coated with natamycin (N) solutions and enriched with essential oils (EOs) were investigated on the chemical (e.g., the rates of pH, dry matter, fat, acidity, salt, protein, water soluble nitrogen, ripening index (RI), 12% trichloroacetic acid-soluble nitrogen, and pH 4.6 solublenitrogen), microbial (e.g., total number of aerobic mesophilic bacteria, lactic acid bacteria in MRS, lactic acid bacteria in M17, coliform and mould) and sensory properties of Kashar cheese during ripeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…They observed significant reduction of mold growth (<1 log [CFU/g]) during the ripening process extended the shelf‐life of cheese when compared to control (2.87 log [CFU/g]) and without any adverse effects on cheese quality. Additionally, Yangilar (2017) obtained similar results when covered Kashar cheese with casein‐wax‐based edible films containing natamycin and essential oils.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…They observed significant reduction of mold growth (<1 log [CFU/g]) during the ripening process extended the shelf‐life of cheese when compared to control (2.87 log [CFU/g]) and without any adverse effects on cheese quality. Additionally, Yangilar (2017) obtained similar results when covered Kashar cheese with casein‐wax‐based edible films containing natamycin and essential oils.…”
Section: Resultsmentioning
confidence: 76%
“…Aires(UBACyT 20020130100176BA, 2014-2017 and UBACyT 20020130100550BA, 2014-2017 and National Agency of ScientificF I G U R E 5 Antimicrobial activity of coatings on Port Salut cheese. Effectiveness of different treatments applied on Port Salut cheese storage at 12°C.…”
mentioning
confidence: 99%
“…A concentration of 1% v/w significantly reduced their growth. In the same study, it was shown that between rosemary and oregano EO, rosemary EO most inhibited coliform growth (Yangilar, 2017). EOs of oregano is able to reduce the growth of E. coli O157:H7 by 1.48 Log and S. aureus by 2.15 Log during storage when applied in whey protein edible films for storage of Kashar cheese (Seydim et al., 2020).…”
Section: Application Of Edible Coatingsmentioning
confidence: 96%
“…Among the most commonly used EOs in edible coating and film formulation we have oregano and rosemary EOs. Yangilar (2017) showed that the addition of 0.5% v/w oregano EO in edible coating for storage of Kashar cheese increased total aerobic mesophilic bacteria counts during 90 days of storage. A concentration of 1% v/w significantly reduced their growth.…”
Section: Application Of Edible Coatingsmentioning
confidence: 99%
“…This preservative is highly effective against mold and yeast growth, but not against bacteria, and is employed in the range of 1–20 ppm [ 94 ]. Yangilar et al [ 104 ] assessed the efficiency of natamycin against mold growth in Kashar cheese after 60 and 90 ripening days using a 0.07% ( w / w ) additive concentration. No sensory differences were observed between control and natamycin-added cheeses.…”
Section: Food Additivesmentioning
confidence: 99%